Psychometric Properties of the COVID-19 Pandemic Fatigue Scale: Cross-sectional Online Survey Study - Carmen Rodriguez-Blazquez; Maria Romay-Barja; Maria Falcon; Alba Ayala; Maria João Forjaz (JMIR Publications, 2022)
BackgroundPandemic fatigue is defined as feelings of demotivation to follow preventive measures against COVID-19, together with decreased trust in government and frequency of information-seeking behaviors. ObjectiveThis study aims to analyze the psychometric properties of the COVID-19-specific pandemic fatigue scale according to classical test theory (CTT) and Rasch model approaches in the general Spanish population. MethodsThis was a cross-sectional study in a representative sample of 1018 adults who completed an online survey in November 2020 in the framework of the COVID-19 Snapshot Monitoring (COSMO)-Spain project. The assessments included the 6-item COVID-19 Pandemic Fatigue Scale (CPFS) and other COVID-19-related variables: COVID-19 infection, adherence to preventive behaviors, information-seeking behavior, self-efficacy, worry, and cognitive and affective risk perception. Data quality, acceptability, reliability, and validity were analyzed according to CTT, and the fit to the Rasch model, unidimensionality, appropriateness of the response scale, item local independency, reliability (person-separation index [PSI]), and item-person distribution were also calculated. ResultsThe mean CPFS score was 17.06 (SD 5.04, range 6-30), with higher scores for women, younger participants, participants who never seek information on COVID-19, those who think they would contract a mild disease in case of infection, those with higher level of worry about coronavirus/COVID-19, and those who felt depressed or felt the coronavirus/COVID-19 is spreading slowly (all P<.01). The Cronbach alpha for the CPFS was 0.74. In the confirmatory factor analysis, one factor was identified (root mean square error of approximation [RMSEA]=.02; comparative fit index [CFI]=.99; χ25=8.06, P=.15). The CPFS showed good fit to the Rasch model (χ 224=42.025, P=.01, PSI=.642), unidimensionality (binomial 95% CI -.005 to .045), and item local independency. ConclusionsOur results suggest that the CPFS has moderate reliability and internal consistency and it is composed of a single dimension. It is a useful tool to ascertain the level of pandemic fatigue in the general population, which may help to guide the communication and information strategies to face the COVID-19 pandemic.